2018
DOI: 10.17344/acsi.2018.4386
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Enzyme-Free Glucose Sensor Based on Electrodeposition of Au Particles on Polyaniline Film Modified Pt Electrode

Abstract: An amperometric non-enzymatic glucose sensor of high sensitivity was developed by modification of Pt electrode with electrodeposition of Au particles on polyaniline film. The Au particles were deposited under optimum growth conditions for maximum dispersion on polymer film to achieve highly sensitive glucose sensor. The characterization of the electrode and the analytical parameters were evaluated using chronoamperometry and cyclic voltammetry techniques. The sensor showed wide linear range from 0.01-8 mM alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A clear oxidation peak appeared at 0.58V and 0.56V for the aSPCE and PAA(DS)/aSPCE, respectively, in the presence of H2O2, which shifted to a lower anodic potential (0.3V) when PtNPs were electrodeposited on the conjugated polymer. Peak intensity sharply increased on Pt@PAA(DS)/aSPCE, which indicated that the synergistic effect of the conjugated polymer and metal nanoparticles improved electrocatalytic activity [25,37,38]. These results demonstrated that Pt@PAA(DS)/aSPCEs possess outstanding electrocatalytic activity toward H2O2 oxidation and high sensitivity, which suggests that they can be used for the real-time monitoring of oxidative stress in living cell suspensions.…”
Section: Electrochemical Characterization Of the Bare/modified Electr...mentioning
confidence: 78%
“…A clear oxidation peak appeared at 0.58V and 0.56V for the aSPCE and PAA(DS)/aSPCE, respectively, in the presence of H2O2, which shifted to a lower anodic potential (0.3V) when PtNPs were electrodeposited on the conjugated polymer. Peak intensity sharply increased on Pt@PAA(DS)/aSPCE, which indicated that the synergistic effect of the conjugated polymer and metal nanoparticles improved electrocatalytic activity [25,37,38]. These results demonstrated that Pt@PAA(DS)/aSPCEs possess outstanding electrocatalytic activity toward H2O2 oxidation and high sensitivity, which suggests that they can be used for the real-time monitoring of oxidative stress in living cell suspensions.…”
Section: Electrochemical Characterization Of the Bare/modified Electr...mentioning
confidence: 78%
“…Electrochemical methods, especially voltammetry, have attracted researchers interest in recent years as it offers a more feasible, cost-effective, and selective determination of the environmental, clinical, and biotechnical targets [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In food quality control, the development of reliable, sensitive and selective methods for fast, precise sensing and quantification of food ingredients and supplements, [1][2][3][4] toxicants, [5][6][7][8][9] antibiotics, and allergens, 10 is an issue of constantly increasing importance. [11][12][13][14][15][16] Recently, as a new direction of the analytical technology is distinguished the development of electrochemical enzymatic biosensorscomplex systems that include an immobilised enzyme (bioelement) and a physical transducer of the signal which may be potentiometric or amperometric, as well as a device for signal reading and processing.…”
Section: Introductionmentioning
confidence: 99%